(untitled) (SCIÉNDO INGENIUM, 2025)
In the present study, the stress behavior in TiN/TaN multilayer films, coated on 0.3 mm thick silicon (100) wafers using the reactive Magnetron Sputtering technique, was investigated. The main objective was to analyze the influence of the substrate bias and the number of bilayers on the residual stress of the thin films, while maintaining a constant total thickness. The coatings were produced in an Ar/N2 atmosphere, with a substrate temperature of 400 °C and bias of -50 V and -250 V. The nanocrystalline structure and morphology of the multilayers were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The stress was determined by measuring the substrate curvature via laser deflection, using the Stoney formula. A transition in the stress behavior from tensile to compressive was observed as the bias voltage was increased from -50 V to -250 V. Specifically, for a bias of -50 V, the stress was tensile, and its absolute value increased slightly with the number of bilayers. In contrast, for a bias of -250 V, the residual stress was compressive, and its absolute magnitude tended to decrease when going from 2 to 4 bilayers, subsequently stabilizing for a higher number of bilayers. These findings demonstrate the possibility of modulating the stress state in TiN/TaN multilayer systems by controlling the bias, which is crucial for optimizing the adhesion and mechanical performance of protective coatings and other surface engineering applications.